IMPROVEMENT OF METHODOLOGY OF DEVELOPMENT OF PHYSICAL EDUCATION AND SPORTS IN GENERAL SECONDARY SCHOOLS: IMPROVEMENT OF METHODOLOGY OF DEVELOPMENT OF PHYSICAL EDUCATION AND SPORTS IN GENERAL SECONDARY SCHOOLS - toshpulatov, rustam (Физическое воспитание, спорт и здоровье, 2025)
The article explores the opportunities and effectiveness of physical education and sports, the involvement of secondary school students in physical education and sports, the inculcation and development of the concept of a healthy lifestyle in them.